Hakikat dan Tujuan Pendidikan Islam - Nasrullah, Muhammad Burhan; Albina, Meyniar (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Islamic education has a deep nature and a clear purpose in shaping the character of individuals and society. The essence of Islamic education is based on the principles of Islamic teachings that emphasize the importance of knowledge, morality, and self-development. The main goal of Islamic education is to guide students to become individuals who are faithful, pious, and have noble character, so that they are able to face various challenges of life wisely. In addition, Islamic education also aims to create a harmonious and just society, where every individual can contribute positively. With a comprehensive approach, Islamic education does not only focus on academic aspects, but also on spiritual, social, and emotional development, making it a means to achieve happiness in this world and the hereafter.